Serum IgE levels and absolute eosinophil counts with treatment response in patients with allergic rhinitis: A prospective study (Panacea Journal of Medical Sciences, 2024)
Introduction: 434-Introduction : Allergic rhinitis (AR) is a highly prevalent, chronic disease, with variable incidence rates. Clinically manifests as nasal discharge, congestion, nasal itching, sneezing and watery eyes. Treatment approach is based on duration and severity of symptoms. Second generation antihistamines are the drug of choice. Serum Ig E and Absolute Eosinophil Counts (AEC) have the potential to be the viable prognostic markers. The present study aims to assess the relationship of Serum IgE and Materials and Methods: AEC with treatment response in patients with allergic rhinitis.40 patients of allergic rhinitis were included in the study and were categorized into mild, moderate and severe allergic rhinitis according to ARIA guidelines. Pre-treatment sample for serum IgE and AEC was taken followed by 4 weeks of medical management according to categories. Post- treatment sample was taken and improvement assessed on the basis of fall in serum IgE and AEC levels.Results: A total 40 patients were enrolled ranging from 14-60 years of age (mean age 28.75±11.23years) with female preponderance (52.5%). Most common presenting symptom being sneezing. Significant decline in pre-treatment AEC and serum IgE levels was observed.Conclusion: The findings of the study indicates that treatment response had an association with AEC and Serum IgE levels.